A Race So Different : Performance and Law in Asian America - Chambers-Letson, Joshua Takano (Book collections on Project MUSE., 2013)
Taking a performance studies approach to understanding Asian American racial subjectivity, the author argues that the law influences racial formation by compelling Asian Americans to embody and perform recognizable identities in both popular aesthetic forms (such as theater, opera, or rock music) and in the rituals of everyday life. Tracing the production of Asian American selfhood from the era of Asian Exclusion through the Global War on Terror, this book explores the legal paradox whereby U.S. law apprehends the Asian American body as simultaneously excluded from and included within the national body politic.